2017
DOI: 10.1186/s13072-017-0135-3
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific regulation of histone H1 phosphorylation in pluripotent cell differentiation

Abstract: BackgroundStructural variation among histone H1 variants confers distinct modes of chromatin binding that are important for differential regulation of chromatin condensation, gene expression and other processes. Changes in the expression and genomic distributions of H1 variants during cell differentiation appear to contribute to phenotypic differences between cell types, but few details are known about the roles of individual H1 variants and the significance of their disparate capacities for phosphorylation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 103 publications
2
22
0
Order By: Relevance
“…These data are consistent with a previous report by our lab, in which pS187-H1.4 was identified as a bonafide substrate for the kinase activity of CDK9 [9], and further verifies the pS187-H1.4 signal. Table 2.…”
Section: X Differential Ps187h14 Signals Enriched At Promoters and supporting
confidence: 93%
See 4 more Smart Citations
“…These data are consistent with a previous report by our lab, in which pS187-H1.4 was identified as a bonafide substrate for the kinase activity of CDK9 [9], and further verifies the pS187-H1.4 signal. Table 2.…”
Section: X Differential Ps187h14 Signals Enriched At Promoters and supporting
confidence: 93%
“…In a more recent study, we showed that the global levels of H1 phosphorylation at H1.5-Ser18 (pS18-H1.5), H1.2/H1.5-Ser173 (pS173-H1.2/5) and pS187-H1.4 are subject to differential regulation and that CDK9 phosphorylated pS187-H1. 4 was associated with maintenance of pluripotency [9]. This provided the first evidence that pS187-H1.4 is may be important for transcriptional activation.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations